Chromatin architecture changes and DNA replication fork collapse are critical features in cryopreserved cells that are differentially controlled by cryoprotectants - Falk, Martin; Falková, Iva; Kopečná, Olga; Bačíková, Alena; Pagáčová, Eva; Šimek, Daniel; Golan, Martin; Kozubek, Stanislav; Pekarová, Michaela; Follett, Shelby E; Klejdus, Bořivoj; Elliott, K Wade; et al. (Scientific reports, 2018)
In this work, we shed new light on the highly debated issue of chromatin fragmentation in cryopreserved cells. Moreover, for the first time, we describe replicating cell-specific DNA damage and higher-order chromatin alterations after freezing and thawing. We identified DNA structural changes associated with the freeze-thaw process and correlated them with the viability of frozen and thawed cells. We simultaneously evaluated DNA defects and the higher-order chromatin structure of frozen and thawed cells with and without cryoprotectant treatment. We found that in replicating (S phase) cells, DNA was preferentially damaged by replication fork collapse, potentially leading to DNA double strand breaks (DSBs), which represent an important source of both genome instability and defects in epigenome maintenance. This induction of DNA defects by the freeze-thaw process was not prevented by any cryoprotectant studied. Both in replicating and non-replicating cells, freezing and thawing altered the chromatin structure in a cryoprotectant-dependent manner. Interestingly, cells with condensed chromatin, which was strongly stimulated by dimethyl sulfoxide (DMSO) prior to freezing had the highest rate of survival after thawing. Our results will facilitate the design of compounds and procedures to decrease injury to cryopreserved cells.
Keywords: Freezing; dimethylsulfoxid; Humans; kryoprezervace; Chromatin; kůže; Dimethyl Sulfoxide; Cryopreservation; Cryoprotective Agents; Skin; MFC-7 buňky; dvouřetězcové zlomy DNA; S Phase; Cell Survival; MCF-7 Cells; viabilita buněk; S fáze; chromatin; zmrazování; lidé; fibroblasty; Fibroblasts; kryoprotektivní látky; DNA Breaks, Double-Stranded